Structural characterization of the Magallanes-Fagnano transform fault, Tierra del Fuego, South America - Palotti, Priscila Fiorella (2013)
Structural analyses in the area of Fagnano and Deseado lakes show different deformational events that took place in the southernmost South America. The compressional structures represent at least two deformational episodes associated with the Upper Cretaceous Andean Orogeny. A series of NE-vergent thrust faults, product of this compression, show that these faults have accommodate some sinistral motion during Upper Cretaceous times. The NE orientation of reverse faults in the Monte Hope area may indicate the later rotation of these faults by the left-lateral strike-slip motion of the Magallanes-Fagnano fault. The secondary faults of the Deseado and Magallanes-Fagnano fault zones fit quiet well with the Riedel shear model, and some of the normal faults cut the Quaternary sediments, indicating a recent activity. These faults may be the evidence of a significant extensional component of the transcurrent system.